Total phenolic, flavonoid, alkaloid and iridoid content and preventive effect of Lider-7-tang on lipopolysaccharide-induced acute lung injury in rats - Erdenechimeg,Ch. (2017)
Lider-7-tang, a medicine used for the treatment of respiratory diseases especially pneumonia and fever in Mongolian Traditional Medicine, was selected for this phytochemical and pharmacological study. The objectives of the study were to determine total biological active substances and analyze the effects of Lider-7-tang treatment in rats with acute lung injury (ALI). Quantitative determination of the total active constituents (phenolic, flavonoid, iridoid and alkaloid) of the methanol extract of Lider-7-tang was performed using Folin-Ciocalteu reagent, aluminum chloride reagent, Trim-Hill reagent, and Bromocresol green reagent, respectively. A total of fifty 8–10-week-old male Wistar rats (200–240 g) were randomized into three groups: control group, lipopolysaccharide (LPS) group (7.5 mg/kg) and LPS+Lider-7 group (90 mg/kg Lider-7-tang before LPS administration). The total content of alkaloids was 0.2±0.043%, total phenols 7.8±0.67%, flavonoids 3.12±0.206%, and iridoids 0.308±0.0095%. This study also evaluated the effects of Lider-7 on levels of inflammatory mediators by observing histopathological features associated with LPS-induced ALI. The rats pretreated with Lider-7 had significantly lower levels of IL-6 (at 3 and 6 h), and TNF-α (at 3, 6, 9, and 12 h). The current study showed that Lider-7 exerted a preventive effect against LPS-induced ALI, which appeared to be mediated by inhibiting the release of pro-inflammatory cytokines.